EOS Microwave Limb Sounder observations of the Antarctic polar vortex breakup in 2004 - Manney, G. L.; Santee, M. L.; Livesey, N. J.; Froidevaux, L.; Read, W. G.; Pumphrey, H. C.; Waters, J. W.; Pawson, S. (American Geophysical Union, 2006)
New observations from the Microwave Limb Sounder (MLS) on NASA’s Aura satellite give a detailed picture of the spring Antarctic polar vortex breakup throughout the stratosphere, with the first daily global HCl profiles providing an unprecedentedly clear view of transport in the lower stratosphere. Poleward transport at progressively lower levels, filamentation, and mixing are detailed in MLS HCl, N2O, H2O, and O3 as the 2004 Antarctic vortex broke up from the top down in early October through late December. Improved MLS H2O data show the subvortex, below the tropical tropopause, breaking up almost simultaneously with the lower stratospheric vortex in December. Vortex remnants persisted in MLS tracers for over a month after the breakup in the midstratosphere, but no more than a week in the lower stratosphere. MLS observations show diabatic descent continuing throughout November, but weak ascent after late October in the lower stratospheric vortex core. Our results extend previous observational transport studies and show consistency with mixing and vortex evolution in meteorological analyses, and with model studies NASA/JPL